"Health for All" in England and Brazil?. (July 2015) - Duncan, Peter; Bertolozzi, Maria Rita; Cowley, Sarah; Egry, Emiko Yoshikawa; Chiesa, Anna Maria; de Siqueira França, Francisco Oscar
This article discusses the achievements and challenges that England and Brazil face in relation to their capacity to address inequalities in health through health promotion and public health policies. Using secondary data (policy texts and related documents), this article contextualizes, explains, and critically appraises health promotion and public health efforts for the reduction of inequalities in health in the 2 countries. A historic documentary analysis was undertaken, with hermeneutics as the methodological framework. The global economic crisis has prompted the so-called developed economies of Europe to reconsider their economic and social priorities. England represents a state facing this kind of challenge. Equally, Brazil is assuming new positions not only on the world stage but also in terms of the relationship it has with its citizens and the priorities it has for state welfare. The United Kingdom continues to finance a health care system allowing universal access in the form of the National Health Service, and state concern about the public health task of reducing inequalities has recently been underlined in policy. For Brazil, although there have been recent achievements related to population access to healthcare, challenges continue, especially with regard to the quality of care